APPLICATION OF VITAMINS IN PEDIATRIC PRACTICE - A.A. Alekseeva (Педиатрическая фармакология)
The problem of balanced nutrition remains to be quite urgent in the modern pediatrics. Despite the fact there are many high quality foodstuffs in the Russian market, the occurrence of the vitamin deficient statuses is still high. The authors of the article describe the important functions of vitamins and microelements in the human body, as well as demonstrate the necessity to additionally administer them as correctly balanced pharmacological forms.Key words: vitamins, vitamin deficiency, correction, children.